The Role Of The Apron Movement Control Unit In Ground Handling Operations - Salsabilla, Shofi; Rochmawati, Laila; Iswahyudi, Prasetyo (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Kalimarau Airport is a Class 1 Airport Service Unit located in Berau Regency, East Kalimantan Province. Is an airport that provides air flight services. To meet the needs of services on the land side and on the air side, the airport cooperates with other parties. Observers conducted research at this airport using observational. To find out the role of the Apron Movement Control (AMC) unit in ground handling operations at Kalimarau Berau Airport. It is hoped that observers will know the use of Ground Support Equipment (GSE) by ground handling officers at Kalimarau Airport. This study uses research methods using qualitative methods and data collection methods, namely using descriptive qualitative methods, namely describing the conditions that occur in the research object. Data obtained from direct observation, literature study, descriptive and interviews. Monitoring the orderliness of ground handling officers is part of Apron Movement Control (AMC) duties. There are markings on the apron that are not yet available at Kalimarau Airport, namely staging area markings that have a function as a place for Ground Support Equipment (GSE) while waiting or standing by on the apron. Some things that can be optimized are increasing awareness of orders among ground handling officers in the use of Ground Support Equipment (GSE). In order to create a safe and orderly Kalimarau airport environment. Some things that can be optimized are increasing awareness of orders among ground handling officers in the use of Ground Support Equipment (GSE). In order to create a safe and orderly Kalimarau airport environment. Some things that can be optimized are increasing awareness of orders among ground handling officers in the use of Ground Support Equipment (GSE). So that the movement of vehicles on the air side can be more directed and safe.